The Effect of Epidural Analgesia on the Delivery Outcome of Induced Labour: A Retrospective Case Series - Angeliki Antonakou; Dimitrios Papoutsis (Obstetrics and Gynecology International)
Objective. To investigate whether the use of epidural analgesia during induced labour was a risk factor for instrumental vaginal delivery and caesarean section (CS) delivery. Study Design. This was a retrospective case series of primigravidae women being induced at term for all indications with a normal body mass index (BMI) at booking and under the age of 40 years. Results. We identified 1,046 women who fulfilled the inclusion criteria of which 31.2% had an epidural analgesia. Those with an epidural analgesia had significantly greater maternal age, higher BMI, greater percentage of oxytocin usage, and a longer first and second stage of labour. Women with an epidural analgesia had a higher instrumental delivery (37.9% versus 16.4%; p<0.001) and CS delivery rate (26% versus 10.1%; p<0.001). Multivariable analysis indicated that the use of an epidural was not a risk factor for a CS delivery but was a risk factor for an instrument-assisted delivery (adjusted OR = 3.63; 95% CI: 2.51–5.24; p<0.001). Conclusion. Our study supports the literature evidence that the use of an epidural increases the instrumental delivery rates. It has also added that there is no effect on CS delivery and the observed increase is due to the presence of confounding factors.